Strategy for Utilizing Lontar Trees (Borassus flabellifer) as Raw Material for Palm Sugar to Improve Family Economy in East Oirata Village, South Kisar District. - Ratusehaka, Sintia; Manakane, Susan Evelin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
Kisar Island, rich in natural diversity, is covered by Lontar trees, which account for nearly a quarter of its area. In the village of East Oirata, staple crops such as corn and Lontar trees are crucial assets for most residents who rely on agriculture and fishing. Although the Lontar tree, known as the tree of 800 uses, has yet to be fully optimized, the processing of Lontar contributes to the local economy. Lontar palm sugar, which is highly nutritious, supports the growing market trend for more natural products. The people of Kisar Island, particularly in East Oirata Village, are striving to enhance the marketing of Kisar palm sugar through innovation and government support, seeing it as an economic opportunity that can improve their well-being. The qualitative research method is an approach that focuses on investigating the conditions of natural objects. Utilizing positivism or interpretive philosophy, the researcher acts as the primary instrument. A holistic understanding is provided through data triangulation, such as observations, interviews, and documentation. Unlike quantitative research, qualitative research produces descriptive and interpretative data processed inductively. This approach allows for in-depth analysis of phenomena, with flexibility and complexity in understanding social, cultural, or behavioural realities. The production process of Lontar palm sugar in East Oirata Village relies heavily on the availability of quality Lontar trees, local knowledge, and experience. Production costs include fixed and variable expenses, with sales significantly contributing to family income. SWOT analysis reveals strengths in resources and capital, weaknesses in production support limitations, opportunities from government attention and high consumer demand, and threats to the availability of supporting materials